1984
DOI: 10.1116/1.572477
|View full text |Cite
|
Sign up to set email alerts
|

The operation of a capacitance manometer at 300 °C

Abstract: The performance of a capacitance manometer operated at 300 °C is described. Calibration against a deadweight primary pressure standard indicates that the stability over a period of 3 months is better than 0.25% of the measured pressure over the pressure range 15–1000 Torr (2.04–131.6 kPa).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Hysteresis effects and zero shifts were found to be insignificant in measurements with this gauge. Buckman et al (1984) investigated the conditions necessary for the operation of the manometer at high temperatures and demonstrated that the calibration can be maintained to within 0·25% for a period of three months.…”
Section: (A) Vacuum System and Pressure Measurementmentioning
confidence: 99%
“…Hysteresis effects and zero shifts were found to be insignificant in measurements with this gauge. Buckman et al (1984) investigated the conditions necessary for the operation of the manometer at high temperatures and demonstrated that the calibration can be maintained to within 0·25% for a period of three months.…”
Section: (A) Vacuum System and Pressure Measurementmentioning
confidence: 99%